Downregulation of nuclear expression of the p33ING1b inhibitor of growth protein in invasive carcinoma of the breast. Issue 7 (1st July 2003) - Nouman, G S; Anderson, J J; Crosier, S; Shrimankar, J; Lunec, J; Angus, B
Abstract : Background/Aims: The inhibitor of growth gene 1 (ING1) is a modulator of cell cycle checkpoints, apoptosis, and cellular senescence. The most widely expressed ING1 isoform is p33 ING1b, which can modulate p53, a molecule that is frequently altered in breast cancer. Reduced ING1 mRNA expression has been observed in primary breast cancer expressing wild-type p53. Methods: p33 ING1b, p53, oestrogen receptor (ER), and progesterone receptor (PgR) expression was studied in 86 primary invasive breast cancers using immunohistochemistry. Results: Reduced nuclear expression of p33 ING1b was found in cancer cells, both in intensity and the proportion of cells staining. This was associated with enhanced cytoplasmic p33 ING1b expression in a proportion of cases. Analysis of several known biological factors indicated that high grade tumours were of larger size and more often negative for ER and PgR expression. However, larger tumours were more frequently p53 negative. These results provide evidence that p33 ING1b alterations are associated with more poorly differentiated tumours. Positive correlations were found between nuclear p33 ING1b expression and both ER and PgR expression. Conclusions: Optimum function of p53 is dependent on p33 ING1b so that a reduction of nuclear p33 ING1b expression, as seen in this series, would be predicted to compromise p53 function. This study showed that p33 ING1b alterations were associated with more poorly differentiated tumours. Therefore, p33 ING1b expression could be used as a marker of differentiation in invasive breast cancer. These results support the view that loss of p33 ING1b may be an important molecular event in the differentiation and pathogenesis of invasive breast cancer.